The Impact of COVID–19 on Albanian Tourism - Sevdie Alshiqi; Arbana Sahiti (Emerging Science Journal, 2022)
Objectives: Nowadays, tourism continues to represent the most dynamic and open part of the countries' economic system. This research paper explores tourism in Albania over the years, with particular focus on the development of tourism during the pandemic situation, mainly the number of entrances and exits of visitors to the country compared to the years before. Methods/Analysis: This study will take into consideration the secondary data provided by the World Travel and Tourism Council and INSTAT Albania focused on 2020 as the pandemic year, compared to the previous years by investigating the movements of visitors in Albania, their origins, and the ways of travel through seaports, air, or land. The travel purposes of Albanian visitors are different, but this research will focus only on those purposes for holidays during the summer season. The data will be presented through the percentage of a frequency distribution at each entrance and exit point, in some cases explained by tables and graphs, comparing the months in the peak summertime. Findings: Statistical analyses represented in this research give a clear picture of developing tourism in Albania during the pandemic year, mostly tourists from Kosovo. Improvement: This research paper summarized some specific recommendations to the government institutions and SMEs specializing in the tourism sector to be ready for the future challenge, even deep dives in the pandemic zone.JEL Classification:N 20, N3 E24, P23 J5 Doi: 10.28991/esj-2022-SPER-03 Full Text: PDF